Material comparison of dynamic cornering fatigue test (iso3006) for automotive wheel rim - Bagherzadeh, Faramarz; Murugesan, Sundeep; Deka, Priyam (International Journal of Engineering and Technology, 2020)
With the technological advancement in the automotive sector, the vehicles are crossing their limits in every aspect. Hence, the subsequent improvement related to the wheel and braking of the vehicle is very crucial as the wheel carries the whole weight of the vehicle in dynamic and harsh environmental conditions. ISO-3006 is a comprehensive test for wheel standardization, and the dynamic cornering fatigue test is a part of this standard. This test investigates the wheel fatigue under bending torque. When a car turns, the bending moment is applied to the wheel via drive axle. In this paper, we investigate the test on a designed wheel with five different materials via ANSYS software. As the wheel weight has a direct impact on vehicle performance, selecting lighter materials is extremely important. The result of this research indi-cates the area of maximum fatigue stresses, and also it provides a comparison between five popular materials for the wheel rim considering the fatigue life and weight of the wheel. Finally, it is shown that carbon fiber reinforced plastic (CFRP) has the most fatigue strength con-cerning its lightweight.